2015
DOI: 10.1097/md.0000000000000566
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and Characterization of 10,282 Randall Plaque-Related Kidney Stones

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 37 publications
2
41
0
4
Order By: Relevance
“…Recent work by Letavernier et al [16] reports data on over 10,000 such stones, each of which showed morphologic signs of having formed on Randall's plaque. Specifically, each stone was identified as showing residue of Randall's plaque, typically as part of a concave region of the stone, suggesting that the stone had formed up against the surface of the papilla.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work by Letavernier et al [16] reports data on over 10,000 such stones, each of which showed morphologic signs of having formed on Randall's plaque. Specifically, each stone was identified as showing residue of Randall's plaque, typically as part of a concave region of the stone, suggesting that the stone had formed up against the surface of the papilla.…”
Section: Resultsmentioning
confidence: 99%
“…In a large series of stones analyzed in a French laboratory using infrared spectroscopy and morphoconstitutional analysis, 34% of 30,149 intact stones collected between 1989 and 2013 that were at least 85% CaOx showed evidence of having formed over Randall’s plaque 11 . Moreover, a marked increase in the frequency of nucleation of stones over plaque occurred between 1990 and 2010 in men and in women, particularly in young adults.…”
Section: Formation Of Idiopathic Calcium Stonesmentioning
confidence: 99%
“…The subsequent formation of CaOx crystals may account for kidney stone formation. As proposed previously, hyperoxaluria is considered a major risk factor for urinary stone, and experimental induction of hyperoxaluria can lead to crystalluria and CaOx crystal deposition in the kidney [6,7]. In addition, recurrent idiopathic stone formers always show mild hyperoxaluria; meanwhile, amount and size of CaOx crystals, alongside disease severity, are highly related to urinary excretion of oxalate (Ox) [8].…”
Section: Introductionmentioning
confidence: 96%
“…With respect to sub-urothelial crystals, injury or degradation of urothelium is considered to play an important role as this leads to crystal exposure to the urinary environment favouring further stone formation. Some scholars speculate that urothelial injury could promote crystal retention and the development of a stone nucleus allowing stone formation on the renal papilla [7,12]. Furthermore, renal cell injury can also promote crystal-cell interaction and crystal retention in the tubules.…”
Section: Introductionmentioning
confidence: 97%